2010
DOI: 10.1007/s00125-010-1836-3
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and healthcare costs of diabetic retinopathy: a population-based register study in Sweden

Abstract: Aims/hypothesis The aim of the present study was to estimate the prevalence and healthcare costs of diabetic retinopathy (DR). Methods This population-based study included all residents (n=251,386) in the catchment area of the eye clinic of Linköping University Hospital, Sweden. Among patients with diabetes (n=12,026), those with and without DR were identified through register data from both the Care Data Warehouse in Östergötland, an administrative healthcare register, and the Swedish National Diabetes Regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
52
3
3

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 92 publications
(69 citation statements)
references
References 24 publications
8
52
3
3
Order By: Relevance
“…The high prevalence of OSA in our sample is consistent with that in other studies of subjects with T2D (6-9). The prevalence of STDR in our cohort (36.1%) is higher than that reported in the literature (5 to 15%) (1,25), reflecting differences in the cohorts and DR risk factors in the various studies.…”
Section: Discussioncontrasting
confidence: 86%
“…The high prevalence of OSA in our sample is consistent with that in other studies of subjects with T2D (6-9). The prevalence of STDR in our cohort (36.1%) is higher than that reported in the literature (5 to 15%) (1,25), reflecting differences in the cohorts and DR risk factors in the various studies.…”
Section: Discussioncontrasting
confidence: 86%
“…Screening procedures have advantages and disadvantages that must be considered [3,4,6]. It has been shown that healthcare costs increase with the severity of diabetic retinopathy , which suggests that preventing its progression may lower healthcare expenditure [7]. In addition, information technology based on epidemiological data may facilitate an individualised determination of screening intervals for diabetic retinopathy [8].…”
Section: Introductionmentioning
confidence: 99%
“…This is a population-based diagnosis-related administrative database that contains information about almost all healthcare contacts within primary care, out-patient clinics and hospital care. The CDW database is run by Östergötland County Council (134)(135)(136). In study III, the number of healthcare visits was self-reported by the patients by answering the following self-developed question: "In the last year, how many times did you seek care due to chest pain?"…”
Section: Healthcare Utilization and Societal Costsmentioning
confidence: 99%
“…The CPP database is also run by Östergötland County Council (134)(135)(136). The indirect costs (Study II) were mainly based on productivity loss due to sickleave, as well as productivity loss due to disability pension in cases of prolonged reduced work capacity.…”
Section: Healthcare Utilization and Societal Costsmentioning
confidence: 99%